Teacher Learning in Difficult Times: Examining Foreign Language Teachers’ Cognitions About Online Teaching to Tide Over COVID-19 - Gao, Lori Xingzhen; Zhang, Lawrence Jun (Frontiers in Psychology, 2020)
The sudden global outbreak of COVID-19 in late 2019 has led to thriving online teaching, including the teaching of languages, across the world. As the online teaching of English-as-a-foreign-language (EFL) in Chinese universities is facing new challenges, EFL teachers have been positively exploring new solutions. To understand how EFL teachers were coping with the challenges, we set up this research as part of a larger study to examine EFL teachers’ cognitions about online teaching in response to the disruption of normal teaching plans. We did so by taking a qualitative approach through analyzing in-depth interviews with three EFL teachers from a Chinese university. Through thematic analysis we found that teachers had clear cognitions about features, advantages, and constraints of online EFL teaching and that they acquired information and communication technology (ICT) literacy through understanding students’ learning needs, online teaching practice, and the necessity of integrating traditional classroom teaching methods into online delivery. We conclude this study with a discussion on its pedagogical implications for similar contexts or colleagues facing similar challenges in other parts of the world.